The Concept of Social Structure - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2006)
Social structure has always been one of the central concepts in classical and contemporary sociological thought. The concept of social structure points to a different articulation of the macro and micro elements of social life. Its meaning has to be understood in the context of the discursive networks in which it is used. The aim of the article is to explore the concept of social structure by making explicit the main conceptual networks from which the different uses of the concept obtain their meaning. We have organized our discussion of social structure around the four paradigms that we have identified as (1) methodological individualism, (2) methodological holism, (3) microsociological ‘theory’, (4) eclectic ‘theory’.